Step
*
1
1
of Lemma
stream-extensionality
1. A : Type
2. x : stream(A)
3. y : stream(A)
4. ∀n:ℕ. (s-nth(n;x) = s-nth(n;y) ∈ A)
5. x1 : stream(A)
6. y1 : stream(A)
7. ∀n:ℕ. (s-nth(n;x1) = s-nth(n;y1) ∈ A)
8. x1 ~ s-hd(x1).s-tl(x1)
9. y1 ~ s-hd(y1).s-tl(y1)
⊢ (s-nth(0;s-hd(x1).s-tl(x1)) = s-nth(0;s-hd(y1).s-tl(y1)) ∈ A)
⇒ (s-hd(s-hd(x1).s-tl(x1)) = s-hd(s-hd(y1).s-tl(y1)) ∈ A)
BY
{ (RecUnfold `s-nth` 0 THEN Reduce 0 THEN Auto) }
Latex:
Latex:
1. A : Type
2. x : stream(A)
3. y : stream(A)
4. \mforall{}n:\mBbbN{}. (s-nth(n;x) = s-nth(n;y))
5. x1 : stream(A)
6. y1 : stream(A)
7. \mforall{}n:\mBbbN{}. (s-nth(n;x1) = s-nth(n;y1))
8. x1 \msim{} s-hd(x1).s-tl(x1)
9. y1 \msim{} s-hd(y1).s-tl(y1)
\mvdash{} (s-nth(0;s-hd(x1).s-tl(x1)) = s-nth(0;s-hd(y1).s-tl(y1)))
{}\mRightarrow{} (s-hd(s-hd(x1).s-tl(x1)) = s-hd(s-hd(y1).s-tl(y1)))
By
Latex:
(RecUnfold `s-nth` 0 THEN Reduce 0 THEN Auto)
Home
Index